Refractory pityriasis rubra pilaris treated with abrocitinib - Filip Rob (Dermatology Reports, 2025)
Pityriasis rubra pilaris is a rare idiopathic papulosquamous disorder that significantly impacts the quality of life and is often refractory to conventional therapies. This study presents a case of successful treatment with an abrocitinib JAK1 inhibitor after several conventional and biologic therapies failed.